Synchrotron X-ray microdiffraction (µXRD) in minerals and environmental research - Gräfe, M.; Klauber, Craig; Gan, B.; Tappero, R. (2014)
Copyright © 2014 International Centre for Diffraction Data.A number of synchrotron X-ray fluorescence microprobes (XFMs) around the world offer synchrotron X-ray microdiffraction (µXRD) to enhance mineral phase identification in geological and other environmental samples. Synchrotron µXRD can significantly enhance micro X-ray fluorescence and micro X-ray absorption fine structure measurements by providing direct structural information on the identity of minerals, their crystallinity, and potential impurities in crystal structures. The information is useful to understand the sequestration of metals in mineral deposits, mineral processing residues, soils, or sediments. Synchrotron µXRD was employed to characterize a surficial calcrete uranium (U) ore sample and to illustrate its usefulness in conjunction with U LIII µXANES analysis. µXRD and U LIII µXANES revealed that the mineral carnotite [K2(UO2)2(V2O8)·nH2O, n = 0, 1, 2, or 3] was not the sole U bearing mineral phase present and that surface complexes and or an amorphous precipitate were present as well. Unit-cell analysis from the µXRD patterns revealed that the interlayer spacing of carnotite was not uniform and that significant unit-cell volume expansions occurred likely because of variable cations (K+, Rb+, and Sr2+) and variably hydrated interlayer cations being present in the interlayer. Oriented specimen, single crystal effects, and the fixed orientation of the sample relative to the incident beam and the charge-coupled device camera limit the number of visible reflections and complicate mineral phase identification. With careful analysis of multiple structural analysis tools available at XFMs, however, a strong link between X-ray amorphous and X-ray crystalline materials in geologic and environmental samples can be established.